JEES 2019
DOI: 10.7176/jees/9-10-01
|View full text |Cite
|
Sign up to set email alerts
|

Review on Role of Proline on Coffee Under Drought Conditions

Abstract: Drought is one of the major constraints that limiting production of crop worldwide. Plants tolerate drought by many ways like morphological, physiological and biochemical tolerance mechanisms. Plants develop mechanisms to tolerant abiotic stress by osmotic adjustment that is usually accomplished by uptake of inorganic ions, as well as the accumulation of proline. Proline is a universal osmo-protectant and acts as an osmolyte and antioxidant, and it is one of the most important compatible solutes that play a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Accumulation of proline is considered an adaptive mechanism in drought-tolerant coffee genotypes. For instance, C. canephora clones (IC-2, IC-3, IC-4, IC-6, IC-8, and R-4) subjected to drought-stress revealed an accumulation of proline with increasing exposure to soil drying, followed by a decline upon re-watering [56]. Moreover, Silva et al [57] showed that proline accumulation was higher in the leaves of a droughttolerant clone of C. canephora than in a susceptible genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of proline is considered an adaptive mechanism in drought-tolerant coffee genotypes. For instance, C. canephora clones (IC-2, IC-3, IC-4, IC-6, IC-8, and R-4) subjected to drought-stress revealed an accumulation of proline with increasing exposure to soil drying, followed by a decline upon re-watering [56]. Moreover, Silva et al [57] showed that proline accumulation was higher in the leaves of a droughttolerant clone of C. canephora than in a susceptible genotype.…”
Section: Discussionmentioning
confidence: 99%
“…In recent study, Tesfaye et al (2020) who evaluated coffee varieties under low moisture stressed areas of southern Ethiopia also reported presence of variation among coffee genotypes in tolerance to moisture stress. Drought tolerance in coffee is due to morphological factors like rooting depth (Pinheiro et al, 2005), physiological including stomatal control of water use (DaMatta et al, 2018), different molecular mechanisms (Vieira et al, 2013) and biochemical such as proline content (Wubishet, 2019). Interestingly, candidate genes for drought tolerance were identified in coffee by high-throughput sequencing in the shoot apex of different Coffea arabica cultivars (Mofatto et al, 2016).…”
Section: Resultsmentioning
confidence: 99%